The effect of benzo[α]pyrene on expression and signaling cross talk of aryl hydrocarbon receptor and NFATc1 in mouse lung tissue. (July 2016) - Parsa, Maliheh; Ostad, Seyed Nasser; Moogahi, Seyed Mohammad Hossein Noori; Bayat, Mohammad; Ghahremani, Mohammad Hossein
Objective: Polycyclic aromatic hydrocarbons (PAHs) are potent environmental pollutants. Benzo[α]pyrene (B[α]P) is the major compound of PAHs that acts by activating aryl hydrocarbon receptor (AhR) in cells. B[α]P is a known carcinogen and an immunotoxicant; however, its role with regard to nuclear factor of activated T cell (NFAT) pathway is unclear. AhR and NFAT signaling pathways have common roles in pathological functions in immunotoxicity and lung cancer. In this study, the effect of AhR activation on expression and signaling cross talk of AhR and NFATc1 pathways in mouse lung tissue has been investigated. Methods: Swiss albino mice were randomly allocated to five groups and administered with cyclosporin A (CsA) and B[α]P for seven constitutive days. Animals were then killed, and lung tissues were obtained after washing the whole blood. Paraffin-embedded blocks were prepared, and 5 µm sections were cut for histopathological and immunohistochemical assessments. The results were scored by observer and digitally analyzed using ImageJ software. Results: Our data showed that CsA administration resulted in a significant reduction of AhR expression. This effect was partly blocked in mice coadministrated with B[α]P and CsA. NFATc1 expression was also reduced in CsA-treated animals. Furthermore, CsA inhibited the pathological effects of B[α]P in mouse lung tissue. Conclusion: AhR expression is dependent on NFATc1 activation, and NFATc1 inhibition remarkably decreases AhR expression. However, it seems that total expression of NFATc1 is not dependent on AhR expression or activation. Moreover, CsA can prevent B[α]P-induced lung tissue damage, and it remarkably decreases NFATc1 expression. The results from this study point toward the molecular interactions of AhR and NFATc1 activation in lung tissue and the benefit of CsA treatment in B[α]P-induced lung damage.